REFORMULATION OF THE MONEY POLITICS PROHIBITION NORM TO ACHIEVE DEMOCRATIC REGIONAL HEAD ELECTIONSI IN INDONESIA - Simanjuntak, Nelson; Pieris, John; Siahaan, Chontina; Hardjono, Hardjono (International Journal of Social Service and Research, 2024)
This study is aimed at determining whether the implementation of the norm prohibiting money politics in Indonesia has been enforced in accordance with existing laws and regulations, and why they have not succeeded in curbing the practice of money politics. This study uses a normative legal research method or doctrinal legal research, supported by empirical research, with a statutory approach and case studies. The study uses secondary data obtained from the literature, including official documents, books, research results in the form of reports, and other forms of data. The results of this study reveal that the very limited time limit, namely 5 working days at Bawaslu to obtain two pieces of evidence and 14 days for the police to conduct an investigation, is the main factor in the low performance of law enforcement for money politics, and the failure of the application of administrative sanctions against candidates who are proven guilty of violating the prohibition on political money in a TSM manner.